A practical approach for putting people in ecosystem‐based ocean planning. Issue 8 (12th September 2014) - Kittinger, John N; Koehn, J Zachary; Le Cornu, Elodie; Ban, Natalie C; Gopnik, Morgan; Armsby, Matt; Brooks, Cassandra; Carr, Mark H; Cinner, Joshua E; Cravens, Amanda; D'Iorio, Mimi; Erickson, Ashley; et al.
Abstract : Marine and coastal ecosystems provide important benefits and services to coastal communities across the globe, but assessing the diversity of social relationships with oceans can prove difficult for conservation scientists and practitioners. This presents barriers to incorporating social dimensions of marine ecosystems into ecosystem‐based planning processes, which can in turn affect the success of planning and management initiatives. Following a global assessment of social research and related planning practices in ocean environments, we present a step‐by‐step approach for natural resource planning practitioners to more systematically incorporate social data into ecosystem‐based ocean planning. Our approach includes three sequential steps: (1) develop a typology of ocean‐specific human uses that occur within the planning region of interest; (2) characterize the complexity of these uses, including the spatiotemporal variability, intensity, and diversity thereof, as well as associated conflicts and compatibility; and (3) integrate social and ecological information to assess trade‐offs necessary for successful implementation of ecosystem‐based ocean planning. We conclude by showing how systematic engagement of social data – together with ecological information – can create advantages for practitioners to improve planning and management outcomes.